Disput o petih paradoksih "poezije stranišča" s prologom in epilogom - Kozak, Krištof Jacek (Amfiteater (Ljubljana), 2023)
Among the works of Taras Kermauner, probably the biggest expert on Slovenian drama and its first theoretician, one can also find a single dramatic experiment: a courtroom debate on the value of avant-garde poetry, based on the case of the accusation against the poet Tomaž Šalamun. While Kermauner develops the genre of judicial disputation in a theatrically fitting and interesting way, he undermines the disputation with an anticlimactic, anti-dramatic conclusion that postpones the decision on the matter to another space-time. A closer examination of the text reveals several conceptual inconsistencies that can be better understood as paradoxes. Thus, the five points that might be defined as paradoxical could be traced in the text itself concerning substantive categories such as the essence of art, the meaning of a nation for art, art and Marxism, and life as the supreme aesthetic category, while the last paradox is a more formal one, since the courtroom debate, with its conclusion, does not reach any point whatsoever. Regardless of the sufficiently clear and pointed presentation of the positions of the two protagonists, the Prosecutor and the Defender, Kermauner decides, rather than escalating the conflict to a (theatrical) climax, to dilute the disputation based on the inclusion of the audience and the conclusion that the latter, in its role as jury, cannot decide for either side. The (dis)solution of the dilemma of the (national, artistic) quality of avant-garde poetry is thus left – despite the fireworks of Kermauner’s theatrical courtroom debate – to the future and literary theory.
Keywords: avant-garde poetry; avantgardistična poezija; courtroom drama; critical realism; kritični realizem; socialist realism; socrealizem; sodna drama; Taras Kermauner; Tomaž Šalamun; values; vrednote